The role of Rh dispersion in gas sensing effects observed in SnO2 thin films [Articol] - Korotcenkov, Ghenadii; Nehasil, V. (Elsevier, 2019)
In the present work the effect of surface modification by rhodium on the conductivity response of the SnO2 films to reducing gases such as CO and H2 and oxidizing gas ozone was analyzed. SnO2 films, subjected to surface modification, were deposited by spray pyrolysis, while Rh was deposited using a micro electron beam evaporation. The thickness of the Rh coating varied in the range of 0–0.1 ML. It was found that there is an optimal thickness of Rh, which gives an improvement in the sensor response and a decrease in the recovery time. An explanation of the observed effects was proposed. It was assumed that the atomically dispersed state of rhodium is most active in gas–sensing effects. The transformation from the atomic state to the cluster state reduces the efficiency of the surface functionalization of SnO2 with rhodium.
Keywords: gas sensor; spray pyrolysis; surface functionalization; clustering